A Nomogram to Predict Regrowth After Ultrasound-Guided Radiofrequency Ablation for Benign Thyroid Nodules - Yan, Lin; Zhang, Mingbo; Li, Xinyang; Li, YingYing; Luo, Yukun (Frontiers in Endocrinology, 2022)
Objective: To develop and validate a nomogram to predict regrowth for patients with benign thyroid nodules undergoing radiofrequency ablation(RFA). Methods: A total of 200 patients with 220 benign thyroid nodules who underwent RFA were included in this respective study. After RFA, patients were followed up at 1, 3, 6, 12 months, and every 12 months thereafter. Regrowth was defined as an increase in nodule volume 50% over the previously recorded smallest volume. A nomogram was developed based on the variables identified by multivariate logistic regression and the model performance was evaluated by discrimination(concordance index) and calibration curves. Results: The incidence of regrowth was 13.64% (30/220) after a mean follow-up period of 27.43±17.99 months. Multivariate logistic regression revealed initial volume(OR=1.047, 95%CI 1.020-1.075), vascularity(OR=2.037, 95%CI 1.218-3.404) and location close to critical structure(OR=4.713, 95%CI 1.817-12.223) were independent factors associated with regrowth. The prognostic nomogram incorporating these three factors achieved good calibration and discriminatory abilities with a concordance index of 0.779 (95%CI 0.686-0.872). Conclusions: A prognostic nomogram was successfully developed to predict nodule regrowth after RFA, which might guide physician in stratifying patients and provide precise guidance for individualized treatment protocols.